An evaluation of alternative fiscal adjustment plans - Nicola Acocella; Elton Beqiraj; Giovanni Di Bartolomeo; Marco Di Pietro; Francesco Felici (ZBW – Leibniz Information Centre for Economics, 2019)
What advice can be given to the policymaker to reduce the burden of public debt after a crisis? In this situation, the debt consolidation calls for fiscal surplus based on increases in taxes and/or reductions in public spending. This paper aims at answering to the above question. Specifically, it evaluates different policy options on the table using the estimated model of the Italian dynamic General Equilibrium Model (IGEM). Our main message is that plans aimed at reducing the public debt based on tax increases rather than expenditure reductions are more effective. Therefore, consolidation should be designed on the former.
Keywords: E60; E62; 330; Austerity; Public debt; Output; Fiscal adjustment plans